Forest fires in Northern region of Portugal: impact on PM levels - Slezakova, Klara (2013)
Every year European citizens become victims of devastating fires, which are especially disastrous for Southern European countries. Apart from the numerous health and economic consequences, fires generate hazardous pollutants that are introduced into the environment, thus representing serious risks for public health. In that regard, particulate matter (PM) is of amajor concern. Thus, the objectives of thisworkwere to characterize the trend of forest fire occurrences and burnt area during the period of 2005 and 2010 and to study the influence of forest fires on levels of particulatematter PM10 and PM2.5. In 2010, 22,026 forest fires occurred in Portugal. The northern region was the most affected by forest fires, with 27% of occurrences in Oporto district. The annual means of PM10 and PM2.5 concentrations at two urban background sites were 25±14 μg m−3 and 8.2±4.9 μg m−3, and 17±13 μg m−3 and 7.3±5.9 μg m−3, respectively. At both sites the highest levels of PMfractionswere observed during July and August of 2010, corresponding to the periods when majority (66%) of forest fires occurred. Furthermore, PM10 daily limit at the two sites was exceeded during 20 and 5 days, respectively; 56%, and respectively 60% of those exceedances occurred during the forest fire season. Considering that the risks of forest fire ignition and severity are enhanced with elevated temperatures, the climate change might increase the environmental impacts of forest fires.